An automated procedure for identification of a person using gait analysis. (5th October 2016) - Galajdová, Alena; Šimšík, Dušan; Rákay, Róbert
Different biometric methods are available for identification purpose of a person. The most commonly used are fingerprints, but there are also other biometric methods such as voice, morphology of ears, structure of iris and so on. In some cases, it is required to identify a person according to his/her biomechanical parameters or even his/her gait pattern. Gait is an outstanding biometric behavioural characteristic that is not widely used yet for identification purposes because efficient and proven automated processes are not yet available. Several systems and gait pattern databases have been developed for rapid evaluation and processing of gait. This article describes an original automated evaluation procedure of gait pattern and identification of unique gait parameters for automatic identification purposes.